Penerapan Pembelajaran Model Problem Based Learning Dengan Pendekatan Culturally Responsive Teaching Berbantuan Video Animasi Guna Meningkatkan Hasil Belajar Siswa Pada Materi Teks Deskripsi Siswa di Kelas VII.2 SMP Negeri 10 Palembang - Nadia Asrobanni; Yessi Fitriani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to apply the Problem Based Learning (PBL) learning model with a Culturally Responsive Teaching (CRT) approach assisted by animated videos to improve student learning outcomes in descriptive text material in class VII.2 of SMP Negeri 10 Palembang. This research uses the classroom action research (PTK) method which is carried out in two cycles. Each cycle involves planning, implementation, observation, and reflection. Trial research subjects in class VII.2 research at SMP Negeri 10 Palembang with a total of 35 students. Collection of observation data, learning results tests, and documentation. Based on the results of research that has been carried out, it can improve the learning outcomes of class VII.2 students at SMP Negeri 10 Palembang. This can be seen from the increase in the percentage of student learning outcomes in cycle I by 71% and in cycle II by 88%. The average value of students' abilities in cycle I was 75.14 and in cycle II 84.85. So it can be concluded that applying the Problem Based Learning (PBL) learning model with a Culturally Responsive Teaching (CRT) approach assisted by animated videos in descriptive text material is able to improve student learning outcomes in class VII.2 of SMP Negeri 10 Palembang.